Functionality of Kenya Prisons Service in Managing Terrorist Prison Criminal Group Activities at Kamiti Maximum Prison, Nairobi Kenya - Kinyanzui, Jane Waithira Kimani (Advances in Social Sciences Research Journal, 2021)
Prisons all over the world have become the ‘epicenter’ of terrorist groups’ activities that include violent extremism, radicalization and recruitments into terrorist prison criminal groups. Although many scholars, especially in Kenya, have not scratched this area, the fact remains that prisons have become a center of terrorist recruitment, strengthening, interconnecting, organizing, and conducting terrorist actions with subjects outside of prison. This study, therefore, was designed to evaluate the Kenya Prisons Service’s functionality in managing Terrorist Prison criminal group Activities at Kamiti Maximum Prison. Three objectives focused this study; to examine the nature of available Terrorist Prison Criminal Groups Management strategies at the institution; to identify the anti-Terrorist Prison Criminal Groups Management gaps, and finally, to identify activities associated with Terrorist Prison Criminal Groups at Kamiti Maximum Prison. The paper employed a descriptive research design and a hybrid methodology where qualitative and quantitative data were obtained. Results showed that the most embraced terrorist management techniques were separation/isolation as it allows for close supervision and use of risk assessment instruments amongst other measures. Results also showed that clandestine use of the internet while in prison was associated with the recruitment of other prisoners into terrorist groups, Islamist militant prison radicalization, and external influences. The study findings showed that the main ways to mitigate the Terrorist Prison Criminal Group activities in Kenya included creating employment opportunities for the youth, creating rehabilitation programs for terror convicts, and offering education to the public. Amongst other measures, this was perceived as mitigation to reduce terrorist groups. The study recommended judges and magistrates to only incarcerate the most serious criminals and prefer non-custodial sentences for petty offenders. This will better manage the radicalization of petty prisoners. Key words: Inmates, terrorist criminals, Prison, Isolation, Concentration, Separation.